Hilar Malignancy: A New Approach For Double MetallicWallstent Placement by Using Combined Percutaneous & Endoscopic Techniques - T. CUMHUR; B. ŞAHİN and T. ÖLÇER and E. ÖZDEMİR and K. ARDA and S. BOYACIOĞLU and C. ÇEKEN (Turkish Journal of Gastroenterology, 2020)
-